ROLE OF CARDIAC-ANKLE VASCULAR INDEX IN PREDICTION OF LONG TERM ADVERSE OUTCOMES IN PATIENTS WITH NON ST ELEVATION ACUTE CORONARY SYNDROME - S. A. Berns; E. A. Schmidt; О. A. Nagirniak; I. I. Zhidkova; М. N. Litvinova; O. L. Barbarash (Кардиоваскулярная терапия и профилактика)
Aim. Evaluation of the association of cardiac-ankle vascular index and development of adverse outcomes in patients after non-ST elevation acute coronary syndrome (NSTEACS).Material and methods. To the registry of NSTEACS in 2009. Totally, 415 patients had been included. The group of main long term (5-year) follow up consisted of 385 persons. Measurement of cardiac-ankle vascular index (CAVI) was done with the VaSera-1000 (Japan) equipment. As the endpoints, death, non-fatal myocardial infarction, unstable angina hospitalization, ischemic stroke were taken. Combination of the outcomes was labeled as combinatory endpoint. Statistics was done with Statistica v.8.0, MedCalc v.16.2.1. For the risk evaluation, the odds ratio (OR) was calculated with 95% confidence interval (95% CI). Differences in the comparison groups were taken as significant with (р)<0,05.Results. The endpoint patients were significantly (p=0,003) older, more commonly had postinfarction cardiosclerosis (p=0,00018) and anamnesis of coronary bypass grafting (p=0,008), higher GRACE score (p=0,00003); brachiocephal arteries stenosis were diagnosed more commonly in this group (p=0,012), as the ischemic ECG changes (p=0,04) and lower ejection fraction of the left ventricle (p=0,0002) at admittance to hospital, comparing with the patients with positive outcome. In patients with adverse outcomes during 5 year follow-up, the right CAVI (p=0,046) and middle CAVI (p=0,04) were significantly higher than in postitive outcome patients. Value of CAVI >8,55 was associated with adverse cardiovascular events in NSTEACS patients during 5 years follow-up, and CAVI ≥9,15 was associated with fatal outcomes.Conclusion. The following clinical and instrumental parameters are associated with adverse cardiovascular events in NSTEMI patients during 5 year follow-up: older age, anamnesis of myocardial infarction and coronary bypass surgery, ischemic ECG changes, decreased left ventricle ejection fraction, higher GRACE score at admission and CAVI >8,55 by sphygmomanometry. This makes possible to use these parameters as the predictors of long term adverse outcomes. Value of CAVI ≥9,15 can be used as a marker of general fatal outcomes in NSTEACS.